Impairment in instrumental activities of daily living with high cognitive demand is an early marker of mild cognitive impairment: the Sydney Memory and Ageing Study. Issue 11 (November 2013) - Reppermund, S.; Brodaty, H.; Crawford, J. D.; Kochan, N. A.; Draper, B.; Slavin, M. J.; Trollor, J. N.; Sachdev, P. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Criteria for mild cognitive impairment (MCI) consider impairment in instrumental activities of daily living (IADL) as exclusionary, but cross-sectional studies suggest that some high-level functional deficits are present in MCI. This longitudinal study examines informant-rated IADL in MCI, compared with cognitively normal (CN) older individuals, and explores whether functional abilities, particularly those with high cognitive demand, are predictors of MCI and dementia over a 2-year period in individuals who were CN at baseline. Method A sample of 602 non-demented community dwelling individuals (375 CN and 227 with MCI) aged 70–90 years underwent baseline and 24-month assessments that included cognitive and medical assessments and an interview with a knowledgeable informant on functional abilities with the Bayer Activities of Daily Living Scale. Results Significantly more deficits in informant-reported IADL with high cognitive demand were present in MCI compared with CN individuals at baseline and 2-year follow-up. Functional ability in CN individuals at baseline, particularly in activities with high cognitive demand, predicted MCI and dementia at follow-up. Difficulties with highly cognitively demanding activities specifically predicted amnestic MCI but not non-amnestic MCI whereas those with low cognitive demand did not predict MCI or dementia. Age, depressive symptoms, cardiovascular risk factors and the sex of the informant did not contribute to the prediction. Conclusions IADL are affected in individuals with MCI, and IADL with a high cognitive demand show impairment predating the diagnosis of MCI. Subtle cognitive impairment is therefore likely to be a major hidden burden in society.